Morphometric comparison at the infraspecific level: assessing the Vachellia caven (Molina) Seigler & Ebinger complex (Caesalpinioideae) in South America - Nicolás, Velasco; Carolina, Pometti; Patrick, Baan; Cristina, Soto-Agurto; Ramiro, Bustamante; Christian, Smit (Phytotaxa, 2026)
Across South America, the Andes mountains have influenced the distribution and morphology of Vachellia caven, a plant species with different climatic ranges on either side of the mountains. The eastern range exhibits six varieties, while the western population s morphology remains underexplored. This study aimed to assess morphological variations across these ranges, focusing on the potential divergence of western Andean populations from their eastern counterparts. We compared herbarium specimens of the six known eastern varieties with those of the western range, and to account for limitations related to the use of herbarium samples, we additionally examined newly collected specimens from both sides of the Andes. Additionally, a common garden experiment was conducted to compare its vegetative morphology growing under the same conditions. Our findings confirmed the distinctiveness of the varieties, although some identification challenges exist. Specifically, A. caven var. caven showed the closest affinity between the two ranges. Notably, while fruit traits were similar across ranges, leaf traits diverged significantly, whether in the field or in the common garden. This study showed for the first time an ongoing trait differentiation between the V. caven populations across the Andes and can be pivotal to transfer varieties name to the new nomenclature.